THE CORPORATE WASTE MANAGEMENT CONFLICT BETWEEN THE SOCIETY AND COMPANY - Awan Setia Dharmawan (Jurnal Partisipatoris, 2019)
Conflict is an attempt to achieve a certain value, status, and authority for a specific benefit as well as to defeat the opponent. The backgrounds of the study were the cause of conflict between the society and the corporate, the form of conflict between the society and the corporate, and the conflict resolution model. This study aims at finding out what caused the conflict between the corporate and the community around Badek river area, the types of conflict occurred, and conflict resolution models. This study applies the qualitative approach and is in the form of descriptive study. This study was conducted in Malang, the urban village of Sukun, Ciptomulyo sub-district. This study used purposive sampling technique to determine the subject of the study. Data collecting technique was by the observation, interview, and documentation. The theory employed in this study is the theory of conflict from Ralf Dahrendorf. The result of the study shows that the conflict between society and corporate arises because of the company’s production waste pollutes the river in the environment where the community lives. The forms of conflict exist are realistic, in-group, open conflict, conflict among different classes, conflict of interest; the conflict resolution model is by using mediation with a compensation mechanism to achieve a win-win solution.